Emodin induced hepatic steatosis in BALb/c mice by modulating the gut microbiota composition and fatty acid metabolism - Xinhua Xia; Xinhua Xia; Xueling He; Jinzhou Huang; Jinzhou Huang; Xuyang Hou; Xuyang Hou; Chen Lin; Chen Lin; Yaxiong Liu; Mei Liu (Frontiers in Pharmacology)
IntroductionThe aim of this study is to examine the physiological effects of emodin on intestinal microorganisms and the liver in the BALb/c mice.Method and ResultsFollowing an 8-week administration of emodin at doses of 25, 50, and 100 mg/kg/day,pathological analyses revealed that emodin significantly reduced the colon length, induced colonic crypt inflammation,diminished the colonic mucus layer,and decreased the fluorescence intensity of colonic tight junction proteins ZO-1 and Occludin. Concurrently, 16S rDNA gene sequencing corroborated that emodin altered the diversity and composition of the intestinal microbiota by increasing the Firmicutes to Bacteroides ratio. Simultaneously, the non-targeted metabolomics analyses exhibited significant alternations in both short chain fatty acids and free fatty acids between the emodin-treated and the normal groups, indicating emodin-induced disturbance in intestinal metabolic disorder. Furthermore, emodin exhibited a significant elevation in LPS levels in colon, serum and liver as well an marked increase in the levels of TC, TG, AST, and ALT in serum. Additionally, histological examination employing by HE and oil-red O staining furtherly verified that the administration of varying doses emodin induced hepatic inflammation and lipid accumulation. Whereas qRT-PCR and Western blot analyses demonstrated that the administering of varying doses of emodin upregulated the mRNA levels of TNF-α, IL-1β, IL-6, and IL-18 as well as the expression of TLR4, Myd88, and P-65. Following the combined administration of probiotics, the high-dose emodin did not significantly influence ALT and AST levels in mice. However, the faeces of the high-dose emodin transplanted in mice and induced a significant increase in AST levels and in the relative abundance of Firmicutes and Proteobacteria.DiscussionThese findings further corroborate that emodin induces liver injury via the intestinal dysfunction. These findings suggested that emodin may disrupt intestinal microbiota and resulted in significant alternations in endogenous metabolites in mice, thereby facilitating the entry of LPS and FFAs into the liver, potentially leading to hepatic injury.